Prediction of Hydrostatic Pressure and Downhole Mud Temperatures While Drilling - I. M. Kutasov; L. V. Eppelbaum (International Journal of Petroleum Technology, 2016)
In deep and hot wells, the densities of water/oil muds and brines (geofluids) can be significantly different from those measured at surface conditions. As a result, bottom-hole pressures predicted with constant mud densities can be in error by hundreds of psig. Determining accurate the density of drilling mud (the density of the formation fluids) under downhole conditions needs for calculating the actual hydrostatic pressure in a well and predicting differential pressure at the bottom-hole. This will help to reduce the fluid losses resulting from miscalculated pressure differentials. In areas with high geothermal gradients, the thermal expansion of drilling muds can lead to unintentional underbalance, and a kick may occur. In this paper we demonstrate the use of an empirical equation for the downhole circulating mud temperature as well as the early derived analytical equation for the drilling mud hydrostatic pressure. A field example is presented.